Staphylococcus sciurias a Reservoir ofmecA toStaphylococcus aureusin Non-Migratory Seabirds from a Remote Oceanic Island - Souza Saraiva, Mauro de Mesquita [UNESP]; Cardoso Gomes de Leon, Candice Maria; Vieira da Silva, Nubia Michelle; Raso, Tania Freitas; Serafini, Patricia Pereira; Naves Givisiez, Patricia Emilia; Gebreyes, Wondwossen Abebe; Bruno de Oliveira, Celso Jose (Mary Ann Liebert, Inc, 2020)
Aim:Genomic analysis of a methicillin-resistantStaphylococcus aureus(MRSA) strain cultured from a non-migratory seabird at Fernando de Noronha Archipelago (Brazilian oceanic islands) was carried out to investigate the potential origin of MRSA genetic determinants in an ecological setting with minimal or absent antimicrobial selective pressure, and minimal interaction with humans and domestic animals. Results:The study determinedmecA gene homology and the phylogenetic relatedness withmecA described inStaphylococcus sciuri, which was the majorStaphylococcusspp. cultured from the birds. Our findings corroboratein silicoassumptions that themecA gene in MRSA strains clinically relevant for humans and animals originates fromS. sciuriancestors. Conclusion:Coagulase-negative staphylococci seem to be natural reservoirs of methicillin-resistant genes toS. aureus, even in environments with very low antimicrobial selection pressure.
Keywords: CoNS; methicillin resistance; Phaethontiformes; Procellariiformes